Early diagnosis of porphyria cutanea tarda as a key to avoiding scarring - a mild form of the disease - Marcela Nowak; Dorota Mehrholz; Wioletta Barańska-Rybak; Roman Nowicki (Termedia Publishing House, 2019)
Porphyria cutanea tarda belongs to the group of porphyrias. Porphyria is a heme disorder caused by an acquired or congenital defect of hepatic enzymes. This consequently leads to the accumulation of porphyrins in various organs. In porphyria cutanea tarda, there is a deficiency of the enzyme uroporphyrinogen decarboxylase. The most frequent factor that leads to damage of this enzyme is drug- or alcohol-induced liver insufficiency. In porphyria cutanea tarda typical clinical manifestations include blisters, erosions, crusts, and milia, that arise predominantly in sun-exposed areas. Furthermore, the skin becomes atrophic, susceptible to injuries and scarring. In our patient, the skin chances were induced by estrogen treatment of endometriosis in combination with UV-exposure. In this case the diagnosisi was established early and significant clinical consequences could be avoided.